2006
DOI: 10.3317/jraas.2006.039
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin type 1 receptor antagonist valsartan attenuates pathological ventricular hypertrophy induced by hyperhomocysteinemia in rats

Abstract: Results from this study suggest that hyperhomocysteinemia-induced hypertension and ventricular hypertrophy in rats are mediated, at least partly; by Ang II activation of AT1-receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…7 Moreover, studies using hypertensive rats showed that Hhe provoked coronary arteriolar remodeling, left ventricular hypertrophy, interstitial fibrosis, and diastolic dysfunction. 8,9 These findings were confirmed by a clinical investigation performed with Framingham Heart Study participants who proved women have a direct correlation between plasmatic Hcy concentration and left ventricular mass and wall thickness. 10 Hhe deleterious effects in cardiovascular system could be associated with different concentrations of Hcy metabolites and alterations in the metabolic pathways.…”
Section: Introductionsupporting
confidence: 74%
“…7 Moreover, studies using hypertensive rats showed that Hhe provoked coronary arteriolar remodeling, left ventricular hypertrophy, interstitial fibrosis, and diastolic dysfunction. 8,9 These findings were confirmed by a clinical investigation performed with Framingham Heart Study participants who proved women have a direct correlation between plasmatic Hcy concentration and left ventricular mass and wall thickness. 10 Hhe deleterious effects in cardiovascular system could be associated with different concentrations of Hcy metabolites and alterations in the metabolic pathways.…”
Section: Introductionsupporting
confidence: 74%
“…By decreasing intracellular levels of ADMA, DDAH1 may prevent angiotensin II-mediated smooth muscle hypertrophy,41 perhaps leading to improved smooth muscle vasodilatory function. This potential mechanism is supported by the observation that the angiotensin II type 1 receptor antagonist valsartan protects from hyperhomocysteinemia-induced ventricular hypertrophy and vascular remodeling 42, 43…”
Section: Discussionmentioning
confidence: 94%
“…This dose is similar to that used in previous studies with this drug in rats [19,20]. Control and normal groups received distilled drinking water only.…”
Section: Valsartan Treatmentmentioning
confidence: 88%